Membaca Representasi Tubuh dan Identitas sebagai Sebuah Tatanan Simbolik dalam Majalah Remaja - Halomoan Manurung, Pappilon (Jurnal Ilmu Komunikasi, 2004)
Teens magazine construct social meaning for teenagers as its audience by positioning them as part of symbolic order of media in particular ways. Teens magazine involves ideas about how be a ânormalâ girl or an ideal girl. The normal girl is a girl who has a boyfriend, shops at mall, hears pop music, etc. The girl who does not do that thing will be categorized her as an outsider. It means, media brings its audiences to a mode of surveillance. Media distincts teenagers to âusâ and âotherâ. This distinction makes some stereotypes and identities for teenagers.